Karakteristik Penggunaan Kosmetik Whitening Cream Pada Ibu Hamil Di Puskesmas Moncobalang Kabupaten Gowa (Window of Public Health Journal, 2025)
Whitening creams are widely used, with most pregnant women at the Moncobalang Community Health Center using them on a regular basis. This high usage highlights the need for public health awareness about potential risks, especially since some products contain mercury. The purpose of this study was to describe the characteristics of whitening cream use among pregnant women at the Moncobalang Community Health Center. This type of research is an analytical study with a cross-sectional study approach. The population and sample of this study were pregnant women at the Moncobalang Community Health Center, with a total sample of 74 pregnant women. The results showed that the characteristics of pregnant women who use cosmetic whitening creams were: the highest age of pregnant women was 17-30 years (64.9%), the highest education level was high school/vocational school (48.6%), and the highest gestational age was 7 months (18.9%). While the highest frequency of use is the frequent category (≥2 a day) as much as 60.8%, the highest volume of use is 10g/month as much as 45.9%, the highest duration of use is the long category (≥3 years) as much as 45.9% and the health impacts felt by pregnant women have a negative impact as much as 82.4%. From the results of the research that has been carried out, it can be concluded that the majority of pregnant women at the Moncobalang Health Center routinely use whitening cream cosmetics every day. It is recommended for pregnant women to stop using whitening cream during pregnancy, because some whitening cream products can contain mercury, which is dangerous and has the risk of causing disorders in fetal growth and development.